Improving Speaking Skills through Tiktok Application: An Endevour of Utilizing Social Media in Higher Education - Rahmawati, Amalia; Syafei, Moh; Prasetiyanto, Moh Aris (Journal of Languages and Language Teaching, 2023)
TikTok is one of the popular applications that contain short-video sharing. Every year, the number of users grows up in every country. They use TikTok not only as the media for entertainment and business but also as the media for learning. The aim of this research is to describe the effect of the TikTok application to improve students’ speaking skills. This research belongs to quasi-experimental research with group pre-post-test design involving 32  students in Diploma of Midwifery Program Universitas Muhammadiyah Kudus as the population. The sampling technique is total sampling with the experimental group (16 students) and control group (16 students). To know the students’ speaking skills, there are four components that must be measured, such as vocabulary, fluency, pronunciation, and comprehension. Moreover, the students’ score has been classified into five categories, they are very good, good, medium, low, and failed. After treatment, the score of speaking ability is improved for the experimental group. The vocabulary increases 45,6%, fluency increases 40,6%, pronunciation increases 31,6%, and comprehension increases 32,8% from the pre-test score. TikTok is a useful application that not only improves  speaking ability but also improves the students’ creativity, motivation, and vocabulary.If the students have wrong in speaking, they not only get the academic punishment but also digital punishment.